Prevalence of early childhood caries among preschool children of tribal Leh district of Ladakh: A cross-sectional study - Tamchos, Rigzin; Rahul, Morankar; Mathur, Vijay Prakash; Tewari, Nitesh; Bansal, Kalpana; Priya, Harsh (Journal of the Indian Society of Pedodontics and Preventive Dentistry, 2025)
ABSTRACT Background: Children from tribal regions in remote geographic locations face several health-related challenges that often remain unnoticed due to a lack of reporting. Untreated dental caries is one such problem with inadequate data from the Himalayan region of Ladakh in north India. This may portray a wrong picture to the policymakers and hence, inadequate efforts to mitigate oral health issues. Aim: This cross-sectional epidemiological study aimed to evaluate the prevalence of Early Childhood Caries (ECC) among three to 6-year-old children in the Leh district of the union territory of Ladakh. Setting and Design: This cross-sectional community (school) based study was conducted among the preschool children of Leh Ladakh. Methodology: The study included 402 preschool children from private and government schools. Oral health status was evaluated in the school premises after consent from the school and parents. The status of ECC was recorded using International Caries Detection and Assessment System II criteria (2005) and oral hygiene by using the Plaque Index (1967). Statistical analysis: The association between the variables was assessed using the Chi-square test. The probability was set at 0.05 to be statistically significant. Result: The overall prevalence of ECC was recorded as 94% (95% confidence interval, 91%-96%). It was found to be 94% in government and 93% in private schools. The most frequently involved teeth were in the mandibular posterior region, whereas maxillary anterior teeth showed the most extensive involvement. The prevalence of ECC is directly proportional to plaque index scores. Conclusion: The prevalence of ECC was found to be very high (94%) among the preschool children of the tribal region in Leh district. It followed the usual pattern of involvement among different dental segments and association with the accumulation of plaque.